THE INFLUENCE OF THE PRODUCT DEVELOPMENT DIVISION MANAGER'S COMMUNICATION STYLE ON THE WORK COMMUNICATION CLIMATE OF PRODUCTION EMPLOYEES AT PT HANES SUPPLY CHAIN INDONESIA - Anisa Cahyaningrum (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study aims to explore how the communication style of the Product Development Division Manager influences the communication climate of production employees at PT Hanes Supply Chain Indonesia. In the context of the manufacturing industry, which is characterized by high performance targets, hierarchical structures, and intensive cross-functional coordination, leadership communication plays a crucial role in shaping the work environment and supervisor–subordinate relationships. This research adopts a qualitative case study approach. Data were collected through in-depth interviews with the manager and production employees in the Product Development Division to capture their experiences, perceptions, and interpretations of everyday communication practices. The data were analyzed using thematic analysis to identify patterns of managerial communication style and their implications for the communication climate. The findings reveal that an open, supportive, and responsive communication style contributes to a more positive communication climate, characterized by higher levels of trust, openness, and psychological safety among employees. In contrast, rigid and less empathetic communication tends to create distance and inhibit open interaction. These results highlight the strategic role of leadership communication in fostering a healthy and productive communication climate within manufacturing organizations.